2017
DOI: 10.1158/1557-3265.ovcasymp16-ap21
|View full text |Cite
|
Sign up to set email alerts
|

Abstract AP21: LIPID DESATURATION IS A METABOLIC MARKER AND THERAPEUTIC TARGET OF OVARIAN CANCER STEM CELLS

Abstract: OBJECTIVES: Lack of sensitive single-cell analysis tools has limited the characterization of the metabolic activity of cancer stem cells (CSCs). The objectives of this study were to identify and target metabolic pathways specifically deregulated in ovarian CSCs. METHODS: We developed a new technique based on hyperspectral stimulated Raman scattering imaging of single living cells coupled with electrospray ionization mass spectrometry (ESI-MS) analysis of extracted lipids to identify unique metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, in cancer de novo fatty acid synthesis may not be fully dependent on SREBP (Williams et al, 2013). For example in Burkitt's lymphoma XBP1s activates SCD expression in a context of high MYC, (Xie et al, JCI, 2018) while desaturases in ovarian stem cells are regulated by NFB (Li et al, 2017). However, the existence of cell type-specific regulators has not been previously established.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cancer de novo fatty acid synthesis may not be fully dependent on SREBP (Williams et al, 2013). For example in Burkitt's lymphoma XBP1s activates SCD expression in a context of high MYC, (Xie et al, JCI, 2018) while desaturases in ovarian stem cells are regulated by NFB (Li et al, 2017). However, the existence of cell type-specific regulators has not been previously established.…”
Section: Discussionmentioning
confidence: 99%
“…Many SCD inhibitors have been developed and tested preclinically. Blockade of SCD leads to reduced content of unsaturated fatty acids and suppression of NF-κB signaling, thereby restraining ovarian cancer stem cells (Li et al, 2017). Combinatory use of SCD inhibitor reverts resistance of lung cancer stem cells to cisplatin and enhances sensitivity of hepatic cancer cells to sorafenib (Ma et al, 2017;Pisanu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidences from preclinical and clinical data support that the cancer stem cells (CSCs) are responsible for tumor recurrence (Peitzsch et al, 2017;Clarke, 2019). Lipid metabolism has been reported as potential target in bulk and CSCs, including CRC (Li et al, 2017;Choi et al, 2019). A previous study showed that blocking stearoyl-CoA desaturase 1 (SCD1) expression or function inhibited the survival of CSCs, but not bulk colorectal cancer cells in vitro and in vivo (Yu et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%